Framing democracy : a behavioral approach to democratic theory - Kelly, Jamie Terence (Princeton University Press, 2012)
The past thirty years have seen a surge of empirical research into political decision making and the influence of framing effects--the phenomenon that occurs when different but equivalent presentations of a decision problem elicit different judgments or preferences. During the same period, political philosophers have become increasingly interested in democratic theory, particularly in deliberative theories of democracy. Unfortunately, the empirical and philosophical studies of democracy have largely proceeded in isolation from each other. As a result, philosophical treatments of democracy have overlooked recent developments in psychology, while the empirical study of framing effects has ignored much contemporary work in political philosophy.